The Role of Competitive Advantage as a Mediation of Digital Marketing on Marketing Performance - Firdaus Yuni Dharta; Luh Komang Candra Dewi; Rulyenzi Rasyid; Ratnawita Ratnawita; Mokhamad Arwani (Yayasan Riset dan Pengembangan Intelektual, 2023)
The objective of this study is to investigate, through an empirical case study of Batik MSMEs in Semarang City, how competitive advantage functions as a mediator between digital marketing and marketing performance. The study's participants were Semarang City's Batik MSME owners. In this study, there were up to 100 respondents in each sample. Data analysis using PLS-SEM is used in this study. The study's findings demonstrate the considerable impact that digital marketing has on competitive advantage. Moreover, there is a notable impact of digital marketing on marketing performance. For There is a noticeable impact of competitive advantage on marketing performance. Additionally, the impact of digital marketing on marketing performance, through the medium of competitive advantage, is particularly noteworthy for Batik MSMEs in Semarang City.